PROFESIONALISME DOSEN DALAM PERSPEKTIF ISLAM DAN KONTRIBUSINYA TERHADAP MUTU PERGURUAN TINGGI - Isna Wardatul Bararah (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2018)
The professionalism of lecturers plays a major role in improving the quality of the learning process in higher education. Lecturers whose main tasks are in the field of teaching are required to have four competencies, academic, pedagogical competencies, personality competencies, and social competencies. One of the mastery learning competencies that the lecturer needs to have in order to create conducive conditions for the student learning process is the competency in mastering the teaching methodology. To measure the four competencies, the government held a lecturer certification program. Certification is the process of providing educator certificates for lecturers held by universities that have an educational staff procurement program that is accredited and determined by the Government, implemented objectively, transparently and accountable. For those who pass the certification, then they get a certificate as a professional lecturer in accordance with the subject matter taught.